SEXUALITY EDUCATION AND ITS IMPACT ON ADOLESCENT REPRODUCTIVE HEALTH KNOWLEDGE IN MANCAR VILLAGE - Sholikhah, Dwi Uswatun; Sari, Gevi Melliya; Kurniawan, Vendi Eko; Rozi, Fahrur (Journal of Indonesian Public Health Service, 2024)
Adolescence is a critical period of transition marked by biological, psychological, and social changes. This community service program aimed to educate adolescents on reproductive health through sexuality education at the Youth Posyandu in Mancar Village, Jombang. Conducted on June 26, 2024, the program involved 15 adolescent participants. It addressed the lack of knowledge about reproductive health and sought to improve adolescents' understanding and attitudes toward their reproductive well-being. A series of activities, including seminars, discussions, and demonstrations, were held to provide comprehensive information on reproductive health. The results showed a significant increase in the participants' knowledge, with 100% of the adolescents demonstrating a good understanding of reproductive health by the end of the program. This initiative highlighted the importance of open access to reproductive health education for adolescents and encouraged parental involvement in discussing reproductive health topics. The program concluded successfully, with participants actively engaging in the learning process and demonstrating increased awareness of reproductive health issues.